Giordano Bruno : een martelaar der vrije gedachte. (Amsterdam : De Dageraad, 1889)
Collectie Vrijzinnige Werkmansbibliotheek
Nederlands
Monografie
Keywords: Bruno, Giordano; Vrijzinnige Werkmansbibliotheek